Da guerra fria à corrida espacial: um recorte interdisciplinar para a educação básica - Santos Júnior, Raimundo Rodrigues dos (2021)
When World Wide War II (1939-1945) had come to an end, the western european countries had lost their leading role on the international scene. The United States (leading the capitalist countries) and Soviet Union (at the top of socialist ones) had to succeed them in the new order. Both intended to spread their influence the world abroad, Americans and Soviets lived in a tense period in the political, ideological, economic and military area, named the Cold War. The scientific and technological rivalry marked that period, which culminated with the space race. The launch of the Sputnik, the first artificial satellite, in 1957, was a landmark produced in the Soviet Union. Four years later, the Soviets launched the Vostok 1 spacecraft, manned by Yuri Gagarin, the first pilot to perform an orbital flight around the world. Although the Soviet came first, the Americans landed the Apollo spacecraft on the lunar surface in 1969, and Neil Armstrong was the first human to arrive there. In the 1970s, the knowledge from the space race were applied, mainly, in artificial satellites development to communications, meteorological e defence, among other services. The amount of historical and scientific information about the space race in the Cold War context contrasts with their insufficiency in the school books nowadays. The educacional product proposed in this text is a paradidactic book that aims the elementary School students to have an interdisciplinary learning, seeing many events in connection to History, Astronomy and Astronautics. Another one educational product came, as a result from the main product, a chapbook, that has a simpler language and popular appeal, but it is guided by the same structure as the paradidactic book.